HEAD NURSE TRANSFORMATIONAL LEADERSHIP TO COMPLIANCE AND WORK MOTIVATION - NATALIA HERLIN KALIGIS (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2021)
Background: Leadership style is a person's behavior in leading a group to achieve certain goals, which can be seen from the superior’s perceptions, subordinates or the leader himself. Transformational leadership will make subordinates feel trusted, valued, loyal and respectful to their leaders, so that subordinates will be motivated to do more than expected. The head nurse, equipped with a transformational leadership style, has a positive impact, which can increase nurse compliance and work motivation. Objective: to analyze the effectiveness of the head nurse transformational leadership style on nurses' compliance to carry out the initial assessment of inpatient care and nurses work motivation in the hospital. Methode: quasi experimental with one group pre post test design. The research was conducted in June-August 2020 in the inpatient room of the Bethesda Tomohon Hospital. Sample: 8 head nurses and 55 nurses in accordance with predetermined criteria. Three data collection tools were used: (1) Observation sheet of Nurse Compliance carrying out the Initial Inpatient Assessment, (2) Nurse Work Motivation Questionnaire and (3) Head Nurse Transformational Leadership Style Questionnaire. Results: There was a significant increase in the compliance of nurses carrying out the initial assessment of hospitalization both before training (p value 0.000) and simultaneously with confounding factors (age, length of work and education p value 0.000), and work motivation (p value 0.005) after a head nurse transformational leadership training intervention was conducted. Conclusion: This means that the transformational leadership style training for the head nurse affects the compliance of nurses in carrying out the initial assessment of hospitalization. This study recommends the need for headnurse transformational leadership style training continuously as an intervention in increasing nurse compliance.